Effects of angiotensin II receptor blockers on the risk factors of coronary heart disease - Azizi bin Ayob (Kulliyyah of Medicine, International Islamic University Malaysia, 2003)
Hypertension seldom occurs in isolation of other risk factors to which it is metabolically linked. Antihypertensive drugs may increase coronary risk by their effect on metabolic risk factors of coronary heart disease. This study was performed to investigate the effects of 2 new antihypertensive drugs, irbesartan and valsartan, which are angiotensin II receptor blockers. A clinical study was carried out to assess the efficacy, clinical acceptability, hypotensive and adverse effect of irbesartan on known metabolic risk factors as well as laboratory parameters in the Malaysian hypertensive populations. Thirty-four mild to moderate hypertensive patients were included in a single blind study over a period of 3 months. Clinic blood pressures were normalized in 76.5% (n=26) of hypertensives patients, and 79.1 % (n=27) of hypertensive patients responded after treatment with 150mg and 300mg daily irbesartan. The proportion of reported adverse events after irbesartan therapy and placebo were 16% (n=8) and 26% (n=l3) respectively. Irbesartan had no significant effect on heart rate and body weight. An extended oral glucose tolerance test (OGTT) was performed at baseline and after 3 months of treatment in 7 hypertensive patients. It was noted that irbesartan had no influence on plasma glucose tolerance and insulin levels. Irbesartan increased plasma basal insulin levels with no effect on glucose levels in hypertensive patients. It also reduced total cholesterol, low density lipoprotein cholesterol and serum uric acid in hypertensive patients. Haematologically, irbesartan reduced erythrocyte count, and increased the mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration and increased leucocyte counts. Irbesartan decreased aspartate aminotransferase levels. The noninvasive 24-hour ambulatory blood pressure monitoring showed that irbesartan significantly reduced mean 24-hour blood pressures but did not influence blood pressure variability. Irbesartan has an acceptable trough to peak effect (>50%) in hypertensive patients. In study to identify plasma total homocysteine (tHcy) levels, included 41 hypertensive patients (34 of them were receiving irbesartan at baseline) and 54 healthy normotensives. The potential effects of irbesartan on tHcy levels were also evaluated. The 95% confidence interval of tHcy levels for healthy normotensive and hypertensive subjects were 3.62 to 13.30μmol/L and 5.58 to 16.42μmol/L, respectively. Male normotensives had higher tHcy levels than their female counterparts. The tHcy levels were significantly higher in hypertensive patients compared to normotensive subjects. A positive association was observed between tHcy levels and diastolic blood pressure in normotensive subjects. Irbesartan produced significant reduction in tHcy levels after 3-month therapy in hypertensive patients. At baseline, there was an inverse relationship between tHcy and plasma insulin, but no significant correlation was observed after irbesartan therapy. Finally, an in vitro experiment was conducted to study the effect of glucose-induced insulin secretion using isolated rat pancreas by the perfusion technique. Concentration of valsartan used was based on the peak plasma concentration with a single standard oral dose of 80mg daily in human. Valsartan significantly increased insulin secretion at all concentrations (0.164mg/L or 1/10 of the peak, 1.64mg/L or at peak, and 16.4mg/L or 10 times of the peak).